2014
DOI: 10.4238/2014.november.7.10
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin inhibitors from Capsicum baccatum var. pendulum leaves involved in Pepper yellow mosaic virus resistance

Abstract: ABSTRACT. Several plant organs contain proteinase inhibitors, which are produced during normal plant development or are induced upon pathogen attack to suppress the enzymatic activity of phytopathogenic microorganisms. In this study, we examined the presence of proteinase inhibitors, specifically trypsin inhibitors, in the leaf extract of Capsicum baccatum var. pendulum inoculated with PepYMV (Pepper yellow mosaic virus). Leaf extract from plants with the accession number UENF 1624, which is resistant to PepYM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…They break down peptides host cell are broken down by proteolytic bacteria and subsequently used either in growth. Protein inhibitors such as trypsin inhibitor are one way to counteract the host against plant pathogens (Moulin et al 2014). Anthocyanins are plant pigments that are also involved in microbial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…They break down peptides host cell are broken down by proteolytic bacteria and subsequently used either in growth. Protein inhibitors such as trypsin inhibitor are one way to counteract the host against plant pathogens (Moulin et al 2014). Anthocyanins are plant pigments that are also involved in microbial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Two C. annuum inhibitors, CapA1 and CapA2, could inhibit trypsin activity by approximately 68% and 91%, respectively. Moulin et al 56 identified trypsin inhibitors in C. baccatum leaves var. pendulum inoculated with Pepper yellow mosaic virus (PepYMV).…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin PI from the leaf extract of Capsicum baccatum var. pendulum inoculated with PepYMV (Pepper yellow mosaic virus) showed a reduction in yellow mosaic viral infection [135] . Cucumis metuliferus serine protease inhibitor (CmSPI) gene, isolated from Cucumis metuliferus which encodes for a serine-type PI (potato I type family).…”
Section: Antiviral Activity Of Spimentioning
confidence: 99%